A Review on AQBD-Based RP-HPLC Method Development for Simultaneous Quantification of Domperidone and Naproxen Sodium in Pharmaceutical Dosage Forms - Vishal V Kendre; Mahesh J Birajdar; Dr. Balaji M Shetkar; Dr.Kranti L. Satpute (Asian Journal of Pharmaceutical Research and Development, 2026)
Analytical Quality by Design (AQbD) has recently become an important methodology used for developing robust analytical techniques.The present review aims at the development of a robust RP-HPLC method for the simultaneous quantitation of Domperidone and Naproxen sodium in the pharmaceutical dosage form utilizing the AQbD principles.Risk assessment tools were employed to identify critical method parameters (CMPs) and critical quality attributes (CQAs), which were then optimized using design of experiment (DoE).A number of chromatographic parameters, such as composition of mobile phase, flow rate, pH, and column choice, have been optimized in order to obtain the optimal resolution and precision.As compared to trial and error techniques, AQbD methodology provides enhanced method robustness and reliability.The developed RP-HPLC method was validated according to the international council for harmonization guidelines, and the specificity, linearity, accuracy, precision, and robustness were established for the simultaneous analysis of two drugs.